2009
DOI: 10.1002/bem.20515
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity microwave irradiation does not substantially alter gene expression in late larval and adult Caenorhabditis elegans

Abstract: Reports that low‐intensity microwave radiation induces heat‐shock reporter gene expression in the nematode, Caenorhabditis elegans, have recently been reinterpreted as a subtle thermal effect caused by slight heating. This study used a microwave exposure system (1.0 GHz, 0.5 W power input; SAR 0.9–3 mW kg−1 for 6‐well plates) that minimises temperature differentials between sham and exposed conditions (≤0.1 °C). Parallel measurement and simulation studies of SAR distribution within this exposure system are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…To date, relatively few studies using large-scale screening have analyzed the effects of ELF-EMF and RF-EMF on gene transcription in organisms, and the results have been contradictory. Some researchers have shown that the transcription levels of some genes are affected by EMF exposure (Olivares-Bañuelos et al, 2004; Remondini et al, 2006; Collard et al, 2011), while others have shown that the transcription profile is unchanged by EMF exposure (Luceri et al, 2005; Paparini et al, 2008; Dawe et al, 2009). Only a few investigations on the effects of EMF on yeast cells have been undertaken, even though their short cell cycle, easy handling, extensive characterization, and eukaryotic genetic background make yeast a good model organism for this type of study.…”
Section: Introductionmentioning
confidence: 99%
“…To date, relatively few studies using large-scale screening have analyzed the effects of ELF-EMF and RF-EMF on gene transcription in organisms, and the results have been contradictory. Some researchers have shown that the transcription levels of some genes are affected by EMF exposure (Olivares-Bañuelos et al, 2004; Remondini et al, 2006; Collard et al, 2011), while others have shown that the transcription profile is unchanged by EMF exposure (Luceri et al, 2005; Paparini et al, 2008; Dawe et al, 2009). Only a few investigations on the effects of EMF on yeast cells have been undertaken, even though their short cell cycle, easy handling, extensive characterization, and eukaryotic genetic background make yeast a good model organism for this type of study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Belyaev et al [2006] reported that in vivo exposure of rat to RF-EMF up-regulated 11 genes and down-regulated one gene in rat cerebellum. Recently, an in vivo study from de Pomerai's group suggested that very low level RF-EMF had no effect on the gene expression in Caenorhabditis elegans [Dawe et al, 2009]. Recently, an in vivo study from de Pomerai's group suggested that very low level RF-EMF had no effect on the gene expression in Caenorhabditis elegans [Dawe et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…elegans (Dawe et al, 2009(Dawe et al, , 2008(Dawe et al, , 2006 though we cannot rule out the Int J Radiat Biol Downloaded from informahealthcare.com by Laurentian University on 12/09/14…”
Section: Discussionmentioning
confidence: 93%